2016
DOI: 10.1590/s1519-99402016000100010
|View full text |Cite
|
Sign up to set email alerts
|

Medidas in vivo e da carcaça e constituintes não carcaça de ovinos alimentados com diferentes níveis do subproduto agroindustrial da goiaba

Abstract: RESUMO O objetivo com este estudo foi avaliar a biometria, morfometria e os órgãos não-componentes da carcaça de ovinos Santa Inês, em confinamento, alimentadas com níveis crescentes (0; 20; 40 e 60% na matéria seca) de subproduto agroindustrial da goiaba como um substituto para o milho. Quarenta ovinos Santa Inês, machos (não castrados), com média de 17,41 ± 1,27kg de peso corporal (PC) e 120 dias de idade no início do estudo, foram utilizados neste experimento. Os animais foram abatidos aos 32kg ou 105 dias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 20 publications
3
12
2
3
Order By: Relevance
“…Thus, the difference found in our study for thoracic perimeter between treatments was not expected since the live weight at slaughtering in the experiment was preset, with no difference for farm live weight. Castro et al (2012), Alves et al (2013), and Silva et al (2016) worked with lambs of the Santa Ines breed and found average values for the thoracic perimeter of 56.14, 65.91, and 71.80 cm, respectively, which are lower than that found in our experiment due to the smaller size breed used by these authors.…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…Thus, the difference found in our study for thoracic perimeter between treatments was not expected since the live weight at slaughtering in the experiment was preset, with no difference for farm live weight. Castro et al (2012), Alves et al (2013), and Silva et al (2016) worked with lambs of the Santa Ines breed and found average values for the thoracic perimeter of 56.14, 65.91, and 71.80 cm, respectively, which are lower than that found in our experiment due to the smaller size breed used by these authors.…”
Section: Resultscontrasting
confidence: 77%
“…Suckling lambs on pasture reached the slaughter weight in a shorter time (83 days) when compared to suckling lambs in confinement, weaned lambs fed roughage, and weaned lambs fed concentrate, which presented an average of 107 days and a higher bone growth. Silva et al (2016) worked with diets with different substitution levels of corn by guava by-product in lamb finishing and found average values of 71.65 cm for hindlimb height.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found a high and positive correlation between body measurements and body weight at slaughter (Fernandes Junior et al, 2015;Silva et al, 2016;Souza et al, 2014). In these studies, the body measurement with the highest correlation with body weight at slaughter was the chest circumference, and consequently this measurement was the one that best predicted body weight at slaughter.…”
Section: Resultsmentioning
confidence: 92%
“…According to Gusmão Filho et al 2009, more developed animals tend to obtain greater body length. However, long animals are not always the best conformed, since the conformation is evaluated by the relationship between muscle profiles, and according to Silva et al (2016), short, wide and compact carcasses are recommended. Values of 66.14 cm and 68.14 cm for withers and croup height observed in this experiment were higher than the 59.45 cm and 61.18 cm observed by Moreno et al (2010b), in Ile de France lambs.…”
Section: Resultsmentioning
confidence: 99%